Advanced nanocomposites for energy conversion technology. (Research'eu results magazine)
'Fuel cells' (FCs), as an efficient conversion technology, can help Europe get passed its energy and environmental challenges. An EU-funded initiative has addressed the various issues restricting the further development of this promising technology.